Comparison of prenatal ultrasound and postmortem findings in fetuses with common pulmonary vein atresia. Issue 6 (22nd May 2019) - Guo, Yong; Gao, Shuang; Kang, Lei; Han, Jiancheng; Zhang, Ye; Weng, Zongjie; Shang, Jianfeng; Hao, Xiaoyan; Zhao, Ying; Ge, Shuping; He, Yihua
Abstract: Background: The previous literature on common pulmonary vein atresia (CPVA) mainly consists of neonatal case reports. There is a lack of research on the prenatal diagnosis of CPVA. Methods: We conducted a retrospective study of all fetuses with CPVA confirmed by autopsy between August 2010 and May 2018. Prenatal echocardiographic features, autopsy findings, and genetic test results were analyzed. We compared fetal CPVA with total anomalous pulmonary venous return (TAPVR) and neonatal CPVA. Results: During the study period, fetal echocardiography was performed on 31 617 fetuses. Six cases of CPVA were identified by autopsies, including 1 case performed with a cardiovascular cast. All 6 cases (100%) had asplenia syndrome (AS) and bilateral superior vena cava (BSVC). In 1 case (16.7%), the prenatal ultrasound results were in complete agreement with the postmortem findings. Four cases (66.7%) were misdiagnosed as TAPVR by prenatal echocardiography. For the remaining case (16.7%), no pulmonary venous anomalies were detected on prenatal echocardiography. No aneuploidy was identified in any of the cases. There were no statistically significant differences among the proportions of associated complex anomalies and AS between the fetal CPVA and TAPVR groups. The proportion of associated complex anomalies and AS in the fetal CPVA group was higher than that in the neonatal group ( P  <   0.05). Conclusions: Prenatal diagnosis of fetal CPVA is difficult and challenging even for experts. Our study showed that fetal CPVA is often combined with AS, complex cardiac malformations, and BSVC. These findings may help in the diagnosis of fetal CPVA.